Synthesis and Production of Sweet-Tasting Protein in E. coli and Purification by Amylose Resin - F. Mansouri (Journal of Sciences, Islamic Republic of Iran)
A sweet water-soluble protein that reminds stable over wide ranges of temperature and pH, Brazzein has various applications. Its tastes like cane sugar but have no calories. However, the extraction of brazzein from its natural source is expensive and not applicable. In this study we used recombinant DNA technology to provide an alternative option for cheaper mass production of brazzein. A brazzein gene was designed, synthesized by using oligonucleotids and cloned into the pBlueScript vector. The synthetic fragment linked to the C-terminal of Maltose-binding protein (MBP) and Glutathion-S-Transferase (GST) for protein expression. The recombinant protein was expressed as a soluble form after induction by IPTG. The fusion protein was purified by amylose resin column and detected by SDS-PAGE. The best yields were achieved by producing brazzein as a fusion with MBP. MBP-brazzein system permits large-scale functional expression and purification of recombinant soluble proteins, providing a basis for the future study of structure and function of brazzein.